Effect of gastric pH on erlotinib pharmacokinetics in healthy individuals: omeprazole and ranitidine. Issue 5 (June 2015) - Kletzl, Heidemarie; Giraudon, Mylene; Ducray, Patricia Sanwald; Abt, Markus; Hamilton, Marta; Lum, Bert L.
Abstract : The aim of this study was to evaluate the effect of coadministration of acid-reducing agents on the pharmacokinetic exposure of orally administered epidermal growth factor receptor inhibitor erlotinib, a drug that displays pH-dependent solubility. Two studies were conducted, the first with the proton pump inhibitor omeprazole and the second with the H2-receptor antagonist ranitidine. Twenty-four healthy male and female volunteers were enrolled in each study. Erlotinib was administered as a single oral 150 mg dose on day 1. After the washout a subsequent study period evaluated 150 mg erlotinib administered with the acid-reducing agent. Omeprazole (40 mg once daily) was given on days 11–14, concomitantly with erlotinib on day 15, and for two additional days (days 16–17). In the ranitidine study, on day 13, participants were randomized to either concomitant dosing (treatment B) or staggered administration (treatment C) of erlotinib and ranitidine and crossed over to the other treatment starting on day 27. For treatment B, ranitidine (300 mg once daily) was administered in the morning for 5 days, 2 h before erlotinib. For treatment C, ranitidine was administered as a divided dose (150 mg twice daily) for 5 days, with erlotinib given 10 h after the previous evening dose and 2 h before the next ranitidine morning dose. Plasma samples were obtained for determination of the concentrations of erlotinib and its metabolite OSI-420, following each erlotinib dose. All participants were monitored for safety and tolerability. The geometric mean ratios of AUC0–∞ and C max for erlotinib and AUC0–last and C max for OSI-420 were substantially decreased when erlotinib was dosed with omeprazole. The estimated mean ratio (90% confidence interval) for erlotinib was 0.54 (0.49–0.59) for AUC0–∞ and 0.39 (0.32–0.48) for C max . For OSI-420, the estimated mean ratio was 0.42 (0.37–0.48) for AUC0–last and 0.31 (0.24–0.41) for C max . AUC0–∞ and C max for erlotinib were substantially decreased by 33 and 54%, respectively, upon coadministration with ranitidine, but the decrease was only 15 and 17% when ranitidine and erlotinib were given staggered. Similar results were observed for the metabolite OSI-420. Erlotinib was generally well-tolerated alone or in combination with omeprazole or ranitidine. Erlotinib pharmacokinetic exposure was substantially reduced upon coadministration with omeprazole and ranitidine, but not when administered with a staggered dosing approach to ranitidine. Therefore, it is recommended that the concomitant use of erlotinib with proton pump inhibitors be avoided. If treatment with an H2-receptor antagonist such as ranitidine is required, erlotinib must be administered 10 h after the H2-receptor antagonist dosing and at least 2 h before the next dose of the H2-receptor antagonist.